A cross‐tissue transcriptome‐wide association study identifies novel susceptibility genes for atrial fibrillation - Yalin Yuan; Xin Zheng; Wenjing Zhang; Zhaoyu Ren; Bin Liang (Journal of Arrhythmia)
Abstract Background Atrial fibrillation (AF), the most common cardiac arrhythmia, has been linked to numerous loci identified by genome‐wide association studies (GWAS). However, the causal genes and underlying mechanisms remain unclear. Methods We conducted a cross‐tissue transcriptome‐wide association studies (TWAS) using the unified test for molecular signatures (UTMOST), integrating genetic data from the FinnGen R11 cohort (287 805 individuals) with gene expression profiles from the genotype‐tissue expression (GTEx) project. To enhance reliability, we applied functional summary‐based imputation (FUSION), fine‐mapping of causal gene sets (FOCUS), and multi‐marker analysis of GenoMic annotation (MAGMA) for gene prioritization, followed by Mendelian randomization (MR) and colocalization analyses. GeneMANIA was used to explore gene functions. Results By integrating four TWAS approaches, this study identified five novel susceptibility genes significantly associated with AF risk. MR analysis further revealed that the gene expression levels of FKBP7, CEP68, and CAMK2D were positively associated with AF risk, while SPATS2L exhibited a significant protective effect. Colocalization analysis demonstrated that CEP68 and SPATS2L share causal variants with AF. Through comprehensive evaluation of multidimensional functional annotations and existing biological evidence, this study highlighted SPATS2L and CEP68 as potential functional candidate genes in AF pathogenesis. Conclusions This cross‐tissue TWAS identified five novel AF susceptibility genes (CAMK2D, SPAST2L, CEP68, FKBP7, and SHRMOO3). Elevated expression of FKBP7, CEP68, and CAMK2D increases AF risk, while SPATS2L showed a protective effect, with colocalization analysis implicating CEP68 and SPATS2L as prioritized candidates. The integration of multi‐omics approaches effectively unravels AF's genetic mechanisms.